Could the gut microbiota reconcile the oral bioavailability conundrum of traditional herbs?. (17th February 2016) - Chen, Feng; Wen, Qi; Jiang, Jun; Li, Hai-Long; Tan, Yin-Feng; Li, Yong-Hui; Zeng, Nian-Kai
Abstract: Ethnopharmacological relevance: A wealth of information is emerging about the impact of gut microbiota on human health and diseases such as cardiovascular diseases, obesity and diabetes. As we learn more, we find out the gut microbiota has the potential as new territory for drug targeting. Some novel therapeutic approaches could be developed through reshaping the commensal microbial structure using combinations of different agents. The gut microbiota also affects drug metabolism, directly and indirectly, particularly towards the orally administered drugs. Herbal products have become the basis of traditional medicines such as traditional Chinese medicine and also been being considered valuable materials in modern drug discovery. Of note, low oral bioavailability but high bioactivity is a conundrum not yet solved for some herbs. Since most of herbal products are orally administered, the herbs' constituents are inevitably exposed to the intestinal microbiota and the interplays between herbal constituents and gut microbiota are expected. Emerging explorations of herb–microbiota interactions have an opportunity to revolutionize the way we view herbal therapeutics. The present review aims to provide information regarding the health promotion and/or disease prevention by the interplay between traditional herbs with low bioavailability and gut microbiota through gut microbiota via two different types of mechanisms: (1) influencing the composition of gut microbiota by herbs and (2) metabolic reactions of herbal constituents by gut microbiota. Materials and methods: The major data bases (PubMed and Web of Science) were searched using "gut microbiota", "intestinal microbiota", "gut flora", "intestinal flora", "gut microflora", "intestinal microflora", "herb", "Chinese medicine", "traditional medicine", or "herbal medicine" as keywords to find out studies regarding herb–microbiota interactions. The Chinese Pharmacopoeia (2010 edition, Volume I) was also used to collect the data of commonly used medicinal herbs and their quality control approaches. Results: Among the 474 monographs of herbs usually used in the Chinese Pharmacopoeia, the quality control approach of 284 monographs is recommended to use high-performance liquid chromatography approach. Notably, the major marker compounds (>60%) for quality control are polyphenols, polysaccharides and saponins, with significant oral bioavailability conundrum. Results from preclinical and clinical studies on herb–microbiota interactions showed that traditional herbs could exert heath promotion and disease prevention roles via influencing the gut microbiota structure. On the other hand, herb constituents such as ginsenoside C-K, hesperidin, baicalin, daidzin and glycyrrhizin could exert their therapeutic effects through gut microbiota-mediated bioconversion. Conclusions: Herb–microbiota interaction studies provide novel mechanistic understanding of the traditional herbs that exhibit poor oral bioavailability. "Microbiota availability" could be taken consideration into describing biological measurements in the therapeutic assessment of herbal medicine. Our review should be of value in stimulating discussions among the scientific community on this relevant theme and prompting more efforts to complement herb–microbiota interactions studies. Graphical abstract: